Thematic Analysis of Al Jazeera Documentary, Unrest Forces Farmers Off Their Land, on Farmer-Herder Conflict in Nigeria - Bello Semiu; Bashirat Damilola Subair; Yusuf Bolokale Suleiman; Odukunle A. Atewolara-Odule (Metacommunication: Journal of Communication Studies, 2025)
The conflict between farmers and herders in Nigeria has, over time, impacted adversely on ethnic tolerance, agriculture, source of livelihood, sheltering and lives of many. In the process, the media have been noted to have exerted a great deal of influence on the perception of people on the array of issues reported by the media. It is against this backdrop that this study sought to examine the portrayal of Unrest forces farmers off their land, a documentary produced by Al Jazeera, on specific themes portrayed in the documentary, government responsibility towards the conflict, the portrayal of language in the documentary and to determine the consequences of the conflict portrayed in the documentary. A qualitative content analysis was performed on the documentary having determined the content categories. The study found that the documentary moderately portrayed peace journalism, government’s inability to do enough in curbing the conflict between farmers and herders, which affected the effectiveness and outcomes of the peace journalism. This is akin to the notation that the media engagement of the conflicting parties, in order to allow them to state their needs, wants and expectations from the other conflicting party and the government, will go a long way in the settlement of the conflict. Therefore, the media are one of the determinants of the escalation or de-escalation of conflict issues. The media should therefore practice continuity in the ways by which they handle conflict issues and to contribute immensely to conflict resolution, peace building of conflict-related issues, to prevent reprisal attacks. More so, the conflict between farmers and herders would subside if government gives adequate attention and act duly in resolving the conflict. Keywords: